Solving the initial condition of the string relaxation equation of the string model for glass transition： part-I - 张晋鲁 王丽娜 周恒为 张丽丽 赵兴宇 黄以能 (Chinese physics B, 2010)
The string model for the glass transition can quantitatively describe the universal a-relaxation in glassformers, including the average relaxation time, the distribution function of the relaxation time, and the relaxation strength as functions of temperature. The string relaxation equation （SRE） of the model, at high enough temperatures, simplifies to the well-known single particle mean-field Debye relaxation equation, and at low enough temperatures to the well-known Rouse-Zimm relaxation equation that describes the relaxation dynamics of linear macromolecules. However, its initial condition, necessary to the further model predictions of glassy dynamics, has not been solved. In this paper, the special initial condition （SIC） of the SRE, i.e. for straight strings and the dielectric spectrum technique that is one of the most common methods to measure the glassy dynamics, was solved exactly. It should be expected that the obtained SIC would benefit the solution of the general initial condition of the SRE of the string model, i.e. for stochastically spatially eonfigurating strings, as will be described in separate publications.